2022
DOI: 10.7554/elife.75228
|View full text |Cite
|
Sign up to set email alerts
|

Boosting of cross-reactive antibodies to endemic coronaviruses by SARS-CoV-2 infection but not vaccination with stabilized spike

Abstract: Preexisting antibodies to endemic coronaviruses (CoV) that cross-react with SARS-CoV-2 have the potential to influence the antibody response to COVID-19 vaccination and infection for better or worse. In this observational study of mucosal and systemic humoral immunity in acutely infected, convalescent, and vaccinated subjects, we tested for cross-reactivity against endemic CoV spike (S) protein at subdomain resolution. Elevated responses, particularly to the β-CoV OC43, were observed in all natural infection c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…Increased eHCoV antibody levels upon SARS-CoV-2 seroconversion have been observed in some cohorts [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] but not others [ 28 , 29 ], and when detected, they have been hypothesized to reflect a boosting of pre-existing cross-reactive responses. We observed significant increases in betacoronavirus but not alphacoronavirus antibody levels (SARS-CoV-1 in the infants and mothers; HCoV-OC43 and HCoV-HKU1 in the mothers) upon SARS-CoV-2 seroconversion compared to the most recent seronegative sample, suggesting that there are cross-reactive antibodies to SARS-CoV-2, which may be more likely to be present in the context of more closely related eHCoVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased eHCoV antibody levels upon SARS-CoV-2 seroconversion have been observed in some cohorts [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] but not others [ 28 , 29 ], and when detected, they have been hypothesized to reflect a boosting of pre-existing cross-reactive responses. We observed significant increases in betacoronavirus but not alphacoronavirus antibody levels (SARS-CoV-1 in the infants and mothers; HCoV-OC43 and HCoV-HKU1 in the mothers) upon SARS-CoV-2 seroconversion compared to the most recent seronegative sample, suggesting that there are cross-reactive antibodies to SARS-CoV-2, which may be more likely to be present in the context of more closely related eHCoVs.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations for this phenomenon have been hypothesized, including the influence of cross-reactive immune responses to endemic human coronaviruses (eHCoVs), also known as seasonal or common colds which cause human coronaviruses. Many studies have shown that eHCoV antibody levels are increased upon SARS-CoV-2 infection [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], which may indicate “boosted” pre-existing memory responses that are cross-reactive. It remains unclear whether such cross-reactive antibody responses could modulate SARS-CoV-2 infection risk.…”
Section: Introductionmentioning
confidence: 99%
“…Increased eHCoV antibody levels upon SARS-CoV-2 seroconversion have been observed in some cohorts [3][4][5][6][7][8][9][10], but not others [18,19], and, when detected, have been hypothesized to reflect boosting of pre-existing cross-reactive responses. We observed significant increases in betacoronavirus, but not alphacoronavirus, antibody levels (SARS-CoV-1 in infants and mothers; HCoV-OC43 and HCoV-HKU1 in mothers) upon SARS-CoV-2 seroconversion compared to the most recent seronegative sample, suggesting that there are cross-reactive antibodies to SARS-CoV-2, and they may be more likely to be present in the context of more closely related eHCoVs.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations for this phenomenon have been hypothesized, including the influence of cross-reactive immune responses to endemic human coronaviruses (eHCoVs), also known as seasonal or common-cold causing human coronaviruses. Many studies have shown that eHCoV antibody levels are increased upon SARS-CoV-2 infection [3][4][5][6][7][8][9][10][11], which may indicate "boosted" pre-existing memory responses that are cross-reactive.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that these higher adaptive immune responses to SARS-CoV-2 may be related to higher preexisting immunity to endemic common cold coronaviruses (HCoVs) in children as compared with adults [ 5 , 19 , 20 ]. Indeed, SARS-CoV-2 cross-reactive T cells and antibodies have been detected in samples collected before the COVID-19 pandemic, and upregulation, or back-boosting, of these responses was observed following SARS-CoV-2 infection [ 21 ]. Evidence for a role of back-boosting of immunity to HCoVs was recently provided by Dowell et al, who showed higher levels of antibodies to beta HCoVs (OC43 and HKU-1) in children as compared with adults following mild or asymptomatic SARS-CoV-2 infection [ 19 ].…”
mentioning
confidence: 99%